2009
DOI: 10.1001/archoto.2008.553
|View full text |Cite
|
Sign up to set email alerts
|

Lingual Osteoma

Abstract: L ingual osteoma is a rare condition, with fewer than 100 cases reported. Because of its rarity, we present an additional case of lingual osteoma that occurred in a 22-year-old woman. This is the first case report, to our knowledge, of a lingual osteoma with preoperative magnetic resonance imaging (MRI) findings described. The epidemiology, clinical presentation, and underlying pathogenesis of this condition are also discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…MRI is also one of the useful imaging modalities in the head and neck region. To the best of our knowledge, only four cases of osseous choristomas that were evaluated with MRI have been reported ( 6 , 19 21 ). Lee et al ( 19 ) indicated that low signal intensity on both T1- and T2-weighted images without enhancement with contrast medium reflects the ossific and calcific nature of the lesion.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…MRI is also one of the useful imaging modalities in the head and neck region. To the best of our knowledge, only four cases of osseous choristomas that were evaluated with MRI have been reported ( 6 , 19 21 ). Lee et al ( 19 ) indicated that low signal intensity on both T1- and T2-weighted images without enhancement with contrast medium reflects the ossific and calcific nature of the lesion.…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, only four cases of osseous choristomas that were evaluated with MRI have been reported ( 6 , 19 21 ). Lee et al ( 19 ) indicated that low signal intensity on both T1- and T2-weighted images without enhancement with contrast medium reflects the ossific and calcific nature of the lesion. If the existence of hard tissue is suspected, X-ray examination and computed tomography (CT) are also useful, as their results can yield further diagnostic confidence ( 19 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On magnetic resonance imaging, osseous choristomas are low signal intensity lesions on T1-and T2-weighted images owing to their ossified and calcified nature. 14 Surgical excision is the most common treatment strategy, 5 although potassium titanyl phosphate laser therapy has also been attempted. 15 There are no reported cases of malignant transformation or postoperative recurrence, 5 thus surgical resection appears to be curative.…”
mentioning
confidence: 99%